Implementing Lymphatic Mapping With Sentinel Node Biopsi in The Management of Patients with Breast Cancer - Nieweg, Omgo (Indonesian Journal of Cancer, 2007)
The past decade has brought major advances in the knowledge about breast cancer. The understanding of the underlying mechanisms of the disease has been increased by molecular biology and this field appears on the brink of becoming part of routine clinical management. The ability to diagnose the disease has been refined. New drugs have been introduced and really improve survival. If one wonders what the most significant recent advance is in the surgical management, then the author submits that lymphatic mapping is it, although he admits maybe being somewhat biased.Lymphatic mapping, also known as sentinel node biopsy, was developed for melanoma at the John Wayne Cancer Center in Santa Monica and was first published by Morton in 1992.1 the principles of the method can be explained in a few sentences. Extracellular fluid enters lymph vessels for transportation back to the blood pool. For purification, the lymph fluid passes through a series of lymph nodes, organized in clusters in specific regions. The sentinel lymph node is the lymph nodes to which the lymph fluid that originates in a primary tumor drains directly through a lymphatic duct. The exfoliated malignant cells that the fluid may contain are filtered out in the lymph node and may reside there. They may proliferate and pass tumor cells on to directly at risk to receive